Brian W. Aldiss - Kincaid, Paul (Modern masters of science fiction., 2022)
"Brian W. Aldiss wrote classic science fiction novels like Report on Probability A and Hothouse. Billion Year Spree, his groundbreaking study of the field, defined the very meaning of SF and delineated its history. Yet Aldiss's discomfort with being a guiding spirit of the British New Wave and his pursuit of mainstream success characterized a lifelong ambivalence toward the genre. Paul Kincaid explores the many contradictions that underlay the distinctive qualities of Aldiss's writing. Wartime experiences in Asia and the alienation that arose upon his return to the cold austerity of postwar Britain inspired themes and imagery that Aldiss drew upon throughout his career. He wrote of prolific nature overwhelming humanity, believed war was madness even though it provided him with the happiest period of his life, and found parallels in the static lives of Indian peasants and hidebound English society. As Kincaid shows, contradictions created tensions that fueled the metaphorical underpinnings of Aldiss's work and shaped not only his long career but the evolution of postwar British science fiction"--